Morphometric Analysis of Posterior Fossa and Foramen Magnum among Pediatric Age Group 6 to 16 Years - Shrestha, B.; Paudel, R. C.; Kashichhawa, S.; Maharjan, N. (Kathmandu University Medical Journal, 2022)
Background Configuration and size of the foramen magnum and posterior cranial fossa plays an important role in the pathophysiology of various disorders like Chiari malformations, basilar invagination etc. Thus, a fundamental knowledge of normal anatomy of this region is important to the clinician for diagnosis and treatment. However, we couldn’t find any anatomical study related to the concerned topic among the pediatric population aged 6 to 16 years in Nepal to the best of our knowledge. Objective To attain the baseline results (volume of bony part of posterior cranial fossa and the surface area of foramen magnum) that will help in the better diagnosis, classification, and treatment of diseases related to posterior fossa and craniovertebral junction and serve as a future reference defining an anatomic range in our region. Method This is a retrospective prospective observational study conducted from 1st February 2021 to 31st January 2022 at Dhulikhel Hospital, Kathmandu University Hospital, Kavrepalanchowk, Nepal. We used convenient sampling technique to fulfil our sample size. We considered 68 patients, who got recruited either from our emergency and OPD departments and were fulfilling our criteria of inclusion. Upon the recruitment, 68 consecutive head CT scan of pediatric patients with normal reports (without any bony or soft-tissue abnormality) were studied. Volume of the posterior fossa was calculated with the help of inbuilt “advanced work station - 3D volume calculator” program in 128 slices - SOMATOM PERSPECTIVE CT Scanner from Siemens, Germany. The area of the foramen magnum was calculated using formula πr2, where r is average radius calculated from obtained antero-posterior and transverse diameter. Result The age of the patients ranged between 6 and 16 years with the mean age of 10.56 ± 3.38 years with male to female distribution of 1: 1.125. The mean volume of the posterior fossa was 165.61 ± 8.52 mm3. The mean AP diameter, transverse diameter, and the surface area of foramen magnum were 3.31 ± 0.12 mm, 2.72 ± 0.12 mm, and 28.60 ± 0.09 mm2 respectively. Conclusion Normal ranges of volume of posterior cranial fossa and various dimensions and surface area of foramen magnum of pediatric population were determined using CT scans, which could serve as future reference in Nepal.